Identifying characteristics associated with performing recommended practices in maternal and newborn care among health facilities in Rwanda: a cross-sectional study - Sipsma Heather L; Curry Leslie A; Kakoma Jean-Baptiste; Linnander Erika L; Bradley Elizabeth H (BMC, 2012)
Abstract Background Although rates of maternal and neonatal mortality have decreased in many countries over the last two decades, they remain unacceptably high, particularly in sub-Saharan Africa. Nevertheless, we know little about the quality of facility-based maternal and newborn care in low-income countries and little about the association between quality of care and health worker training, supervision, and incentives in these settings. We therefore sought to examine the quality of facility-based maternal and newborn health care by describing the implementation of recommended practices for maternal and newborn care among health care facilities. We also aimed to determine whether increased training, supervision, and incentives for health workers were associated with implementing these recommended practices. We chose to study these aims in the Republic of Rwanda, where rates of maternal and newborn mortality are high and where substantial attention is currently focused on strengthening health workforce capacity and quality. Methods We used data from the 2007 Rwanda Service Provision Assessment. Using observations from 455 facilities and interviews from 1357 providers, we generated descriptive statistics to describe the use of recommended practices and frequencies of provider training, supervision, and incentives in the areas of antenatal, delivery, and newborn care. We then constructed multivariable regression models to examine the associations between using recommended practices and health provider training, supervision, and incentives. Results Use of recommended practices varied widely, and very few facilities performed all recommended practices. Furthermore, in most areas of care, less than 25% of providers reported having had any pre-service or in-service training in the last 3 years. Contrary to our hypotheses, we found no evidence that training, supervision, or incentives were consistently associated with using recommended practices. Conclusion Our findings highlight the need to improve facility-based maternal and newborn care in Rwanda and suggest that current approaches to workforce training, supervision, and incentives may not be adequate for improving these critical practices.